History repeating itself: Arnaud's case of pathological déjà vu. (February 2017) - Bertrand, Julie M.F.; Martinon, Léa M.; Souchay, Céline; Moulin, Chris J.A.
Abstract: We present a translation of Arnaud's (1896) case report of Patient Louis, a case he describes as having a pathological form of déjà vu. Louis has the delusional belief that the present moment is a repetition of an exact same previous event. Arnaud's paper is critical for two reasons. Firstly, it is amongst the first articles in the scientific literature to describe the déjà vu experience using the term 'déjà vu'. Secondly, the case report of someone with delusional and persistent déjà vu, anticipates recently reported cases with similar symptoms, which are beginning to gain interest as a particular form of memory disorder. We offer a contemporary analysis of Louis and conclude that, whilst the article was critical in the development of déjà vu as a scientific concern, Louis's distorted memory is not best described as déjà vu, but rather as a form of reduplicative paramnesia described as recollective confabulation.